The Joint Efforts of Indonesian and Australian Governments in Countering Terrorism: Intelligence Cooperation - Nibras Khairunnisa Ramadhani; Muhammad Hikam; Fahlesa Munabari (Deviance Jurnal kriminologi, 2021)
Terrorism has become a global threat particularly since the 9/11 September tragedy. In Indonesia, acts of terrorism have become a great concern among many stakeholders of the Indonesian government particularly in the aftermath of the Bali Bombing incidents in the beginning of 2000s. The incidents took many lives, and many of them were Australian citizens. As a result, Australia offered Indonesia assistance in the form of cooperation in a variety of areas, including infrastructure and forensics training for police officers. This article aims to analyze the depth and dynamics of Indonesia – Australia intelligence cooperation that contribute to reduce the acts of terrorism in Indonesia. Employing the perspectives of international cooperation and human security, the article argues that the primary driving factor that facilitates Indonesia and Australia cooperation in the areas of counterterrorism and intelligence that the countries face the same terrorism threats that, if not anticipated comprehensively, would endanger the security stability in respective countries and in the Asia-Pacific region.